Television as total practices and liberalization of distinctions. The Ukrainian case - Natalia Kostenko (Pontifícia Universidade Católica do Rio Grande do Sul, 2009)
The simultaneous effect of two opposite tendencies is peculiar to the Ukrainian television as well as to most national media. Firstly, communication assumes more and more universal character due to expansion of the access to the media and because of the standard content. At the same time cultural, social and political distinctions of communications free themselves as the result of the media market's influence. Both tendencies exhibit internal contradictions and counteractions. The obvious heterogeneity of viewer's preferences opposes the total entertainment effect of the media reality and essential resistant potential of the Ukrainian audience as well as low level of trust in political media oppose total control over political preferences of the viewers. It would seem that the articulation of distinctions corresponds to the real life styles of population, but in fact it turns out to be a fixation of the traditionally established division into cultural competent and undemanding audiences, a strengthening of "mechanical" pluralism sanctioned by media business. The situation with the Ukrainian media is considered on the basis of the results of sociological researches conducted by the Institute of sociology of National Academy of sciences of Ukraine in 2000-2007.